A study on the characteristics of Ozone Weekend Effect and reaction sensitivity in Chengdu. Issue 1 (March 2020) - Liu, Hefan; Deng, Ye; Huang, Fengxia; Zhang, Tianyue; Yang, Xinyue; Zhang, Xin; Song, Danlin; Chen, Yan
Abstract: This study improved the computation theory "Ozone Weekend Effect Method" (OWEM) and analyzed the 2016 observation data from the state-controlled ambient air quality monitoring sites in Chengdu using the OWEM theory. The improved OWEM theory is then applied to processing large sample data and making a judgment on photochemical reaction sensitivity in Chengdu. The result of applying the OWEM theory to Chengdu shows 1) that the VOCs-limited period, the NOx-limited period and the photochemical reaction steady-state period, Rt, accounted for 66.06%, 33.64% and 0.30%, respectively; 2) that on a seasonal basis, i.e. in the ozone photochemical reaction occurring in spring, summer, autumn and winter 2016 in Chengdu, the VOCs-limited period accounted for 59.40%, 72.49%, 63.85% and 68.49% of the 2016 observed data, respectively, and the NOx-limited period accounted for 39.70%, 27.51%, 36.15% and 31.19%respectively; 3) that in the VOCs-limited period and the NOx-limited period of August 2016, the month when the most serious ozone pollution of that year occurred in Chengdu, Rt accounted for 70.0% and 30.0%, respectively, and that there was no photochemical reaction steady-state zone period that month; 4) and that through estimation, it is suggested that as for the ozone pollution control of Chengdu, the ratio of VOCs emission reduction to NOx emission reduction should be around 3:1.